Integration Profile – An Innovative New Methodology for Comparing Regional Integrations - Ráti, József (Public Finance Quarterly, 2025)
The role of regional cooperation has become more important as economic blocs have gotten stronger, the pandemic has caused disruptions, and new geopolitical challenges like deglobalization and protectionism have popped up. The Economics of Regional Integration analyzes theoretical and empirical approaches to regional integration processes through ten different regional examples. The most innovative feature of the book is the development of a new composite indicator ("integration profile") that measures the economic, social, and institutional dimensions of integration, providing a practical tool for policymakers and researchers to assess regional integration. Although primarily European in focus, the book is an important step towards a deeper, comparative understanding of regional integration.